Estimating revenues from offshore wind-storage systems: The importance of advanced battery models. (15th October 2020) - Jafari, Mehdi; Botterud, Audun; Sakti, Apurba
Highlights: Six battery modeling approaches are investigated. Without proper battery representations revenues are overestimated by 35%. The battery system, when located onshore, yielded higher revenues. Energy- and capacity-market revenues insufficient for the battery to breakeven. Battery breakeven costs found to be in the range of $50–115 per kWh. Abstract: We investigate six different lithium-ion battery modeling approaches to highlight the importance of accurately representing batteries in decision tools. Advanced mixed-integer-linear battery models account for efficiencies as a function of the discharge power, power-limits as a function of the state-of-charge, along with degradation, which are usually not accounted for in power systems models. The revenue potential from offshore wind paired with battery systems is then examined using the more advanced representation where degradation is the sum of the capacity fades resulting from calendar- and cycle-aging. The impacts of variability of offshore wind output along with energy- and capacity-market prices are evaluated using publicly available data from 2010 to 2013 using NYISO as a test case. For 2013, results highlight that without accurate battery representations, models can overestimate battery revenues by up to 35%, resulting primarily from degradation-tied costs. Advanced dispatch algorithms that account for calendar- and cycle-aging of the battery can help operate the battery more efficiently. Locating the battery onshore yields higher revenues and with wider useable SOC windows, it is possible to monetize higher arbitrage opportunities, which can compensate for any additional degradation-tied costs. The added value of a MWh of energy storage varies from $2 to $4.5 per MWh of wind energy, which leads to a breakeven cost range of $50–115 per kWh for the battery systems. As such, energy- and capacity-market revenues were found to be insufficient in recovering the investment costs of current battery systems for the applications considered in this analysis.